KONFLIK LATEN ANTARA PENGANUT AGAMA SIKH DAN TAMIL DI KOTA MEDAN - Rholand Muary (Jurnal Ilmiah Sosiologi Agama (JISA), 2018)
This research discusses the latent conflict between Sikhs and Tamils in Medan. This study uses conflict theories with the approaches of latent conflict and the sources of conflict itself. This research is intended to look at the hidden forms of conflict on the relationship of Sikhs with Tamil as well as written attempts to conflict between the two. This research uses qualitative research methods, where researchers directly observe the community and try to analyze every subjective and objective experience in sociology of religion approach. Informants in this research are religious leaders and community of Sikh and Tamil. The results of this study reveal that there are latent conflict between Sikh and Tamil community. Latent conflicts can be grouped in several aspects, among others, on religious-cultural aspects, political aspects as well as socio-economic aspects. In the handling of latent conflicts between both religion, it is necessary for the state and society to pay attention so the conflict not to extend to open conflict.